STRATEGIC HUMAN RESOURCE OUTSOURCING, ENTERPRISE RESOURCE PLANNING, AND PERFORMANCE: A SYSTEMATIC REVIEW - A.D. ALAGAH (Scholar Express Journals, 2021)
This paper x-rays how organizations can adopt strategic human resource outsourcing to enhance performance as professionals today are constantly seeking out ways to drastically reduce their day-to-day overhead operations cost to better focus on their core competencies. To survive in a fast-changing business environment, organizations must strategize and make high performance its default state. There has been considerable anecdotal evidence that suggests that the use of outsourcing strategy greatly influence higher levels of performance. This has further demonstrated that strategic human resource outsourcing activities seemingly have lasting positive implications which has mostly resulted in several positive outcomes within the context of performance such as operational cost efficiency and firm operational excellence. Thus, the paper recommends that management of organizations should consider adopting strategic human resource outsourcing as it offers organizations an opportunity to reduce operational cost so as to keep the organization in business. Furthermore, organizations should engage in enterprise resource planning to enable them source, obtain, and interpret information so that they can make informed decision regarding strategic human resource outsourcing to enable them gain competitive edge.
Keywords: Strategic Human Resource; Outsourcing; Transactional Cost; Operational Cost Efficiency